Formation of Value Orientations of Profile Classes Pupils of a General Educational School during Teaching of a New Management Paradigm – Creativity Management - Канафоцька, Галина Павлівна (Educological discourse, 2014)
The article reveals the results of the introduction of innovative techniques of teaching that are based on the new management paradigm – creativity management. The purpose of creativity management as innovative teaching model consists of forming a holistic person with high level of consciousness, self-discipline, moral ethical behaviour norms and understanding of social responsibility for results of made decisions. They are ready to search their own mission in result of using the creative beginnings and understanding of leadership-service in the future. The objected technique is personal and team-focused and consists of knowledge and educational components that allows to reveal not only pupils’ creative abilities but to form value orientations of each creativity subject.